Effect of Pithecellobium jiringa as antimicrobial agent - Abu Bakar, Ruzilawati; Ahmad, Imran; Sulaiman, Shaida Fariza (Bangladesh Journal of Pharmacology, 2012)
Pithecellobium jiringa is Malay traditional local delicacy. There is no local data on antimicrobial nature of P. jiringa is available. The objective of our study was to evaluate the antimicrobial activity of P. jiringa. Leaves, pods and seeds of P. jiringa were extracted using methanol. Ten test microorganisms were used in the study. The disc diffusion assay was used to determine the sensitivity of the samples, while the liquid dilution method was used for the determination of the minimal inhibition concentration (MIC). Chloramphenicol was used as a reference standard. The results revealed that all extracts of P. jiringa showed the antimicrobial and antifungal activities against the test organisms. Amongst the active extracts, the minimal inhibition concentration (MIC) determination showed that the extract of P. jiringa leaf was the most active against S. aureus, S. epidermidis and M. gypsum (100 mg/mL). The results provided evidence that the studied plants extract might be potential sources of new antimicrobial drug.